An Econometric and Socio-Psychological Analysis of the Education Migration Processes - Cherusheva, G. B.; Parkhomenko, V. V. (Statistics of Ukraine, 2019)
The Ukraine’s integration in the European and global education area and its implications for the academic mobility processes call for understanding the ways and prospects of modernization of the Ukraine’s strategy on exports of education services, strengthening of its position on the international market of education services, intensification of information efforts abroad aiming to convince potential students in the attractiveness of training in Ukraine and wide perspectives of the Ukrainian higher education. The article contains an analysis of the results from an empirical econometric and socio-psychological study devoted to the problems of academic mobility and education migration of Ukrainian youth and foreigners in Ukraine. A comparative analysis of the data shows that education migration processes have similar parameters for foreign students in Ukraine and Ukrainian abroad. The data on the attractiveness of the Ukrainian education for foreign students are analyzed as part of the study, with identifying the factors with impact on the scopes of student migration. The tendency of the continually increasing interest in higher education in Ukraine, in spite of the difficulties (political and economic) faced by Ukraine, is revealed, which is confirmed by the growing numbers of both foreign students in Ukraine and the higher education institutions in which they study. An analysis of the data shows that the education in Ukraine is the most attractive for post-soviet countries. Also, the numbers of education migrants coming from Africa and Asia, in particular from India, Morocco, Nigeria, Egypt, Israel, Jordan, Turkey, and Ghana, have been stably increasing in 2013–2019. An analysis of interviews reveals that foreign students go to study in Ukraine due to the following motives: the possibility to get high quality education (and return to a home country); low education fees compared with a home country; the optimal “price-quality” ratio etc. It was found out which specialties of the professional training drew special interest of foreign students. It is shown that the flows of education migration of Ukrainian students to other counties tended to intensify in the latest five years. The education migration was growing year-by-year in 2013/14–2017/18. According to the official statistical data on education migration recorded for 2017/2018, the number of Ukrainians taking education course in other countries reached 76181. The most attractive countries for training of Ukrainian youth and the essential factors behind their choice of country for education are defined. The estimated cost of education programs in selected countries that are the most attractive for Ukrainian youth is analyzed as of the academic period 2017/2018. It is found out that the prevailing motives for Ukrainians seeking education in other countries are professional and socio-cultural values: higher quality education; better training conditions; good carrier prospects; learning of foreign languages; learning about other cultures. The conducted studies that included student interviews revealed the reasons for the education migration of Ukrainians: inadequate level of professional training in domestic higher education institutions; problems with future job placement with domestic diplomas; corruption; lack of stability in the country and blurred prospects of change for the better. The conducted study enables to highlight the problematic points of the education migration in Ukraine and outlined the essential steps to reduce the migration flow of Ukrainian youth.